Osteo-regeneration personalized for children by rapid maxillary expansion: an imaging study based on synchrotron radiation microtomography - Alessandra Giuliani; Serena Mazzoni; Carlo Mangano; Piero Antonio Zecca; Alberto Caprioglio; Nicolò Vercellini; Mario Raspanti; Francesco Mangano; Adriano Piattelli; Giovanna Iezzi; Rosamaria Fastuca (BMC, 2018)
Abstract Background Personalized maxillary expansion procedure has been proposed to correct maxillary transversal deficiency; different protocols of stem cell activation have been suggested and rapid maxillary expansion (RME) is the most commonly used among clinicians. The present study aimed to quantify in three-dimensions (3D) the osteo-regeneration of the midpalatal suture in children submitted to RME. Methods Three patients (mean age 8.3 ± 0.9 years) were enrolled in the study to preform biopsy of midpalatal suture. Two patients (subjects 1 and 2) were subjected to RME before biopsy. The third patient did not need maxillary expansion treatment and was enrolled as control (subject 3). Midpalatal suture samples were harvested 7 days after RME in subject 1, and 30 days after RME in subject 2. The samples were harvested with the clinical aim to remove bone for the supernumerary tooth extraction. When possible, maxillary suture and bone margins were both included in the sample. All the biopsies were evaluated by complementary imaging techniques, namely Synchrotron Radiation-based X-ray microtomography (microCT) and comparative light and electron microscopy. Results In agreement with microscopy, it was detected by microCT a relevant amount of newly formed bone both 7 days and 30 days after RME, with bone growth and a progressive mineralization, even if still immature respect to the control, also 30 days after RME. Interestingly, the microCT showed that the new bone was strongly connected and cross-linked, without a preferential orientation perpendicular to the suture's long axis (previously hypothesized by histology), but with well-organized and rather isotropic 3D trabeculae. Conclusions The microCT imaging revealed, for the first time to the authors' knowledge, the 3D bone regeneration in children submitted to RME.